Recommended Requirements for the Validation and Application of Scales and Methods in the Field of Diagnostics and Provision of Medical and Psychological Assistance - Chaban Олег; Burdeinyi Андрій (Psychosomatic Medicine and General Practice, 2024)
Relevance. Modern medical and psychological challenges, such as post-traumatic disorders, depression, anxiety states, and post-COVID syndrome, require an accurate and systematic approach to diagnosing and assessing patients’ conditions. The use of validated scales allows professionals to make informed decisions based on data, contributing to effective assistance. Furthermore, scientific progress and constant changes in treatment standards necessitate the updating and improvement of methodologies for their application in various clinical and psychological contexts. The recommendations will help standardize approaches to the assessment of tools, ensuring high-quality diagnostics and treatment, regardless of the location or specific issues faced by the patient. Aims. To provide scientifically substantiated standards for the validation and effective use of diagnostic scales and methods in medical and psychological assistance, contributing to the enhancement of diagnostic quality and optimization of treatment approaches to improve patient outcomes.